PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP HASIL USAHATANI PADI, JAGUNG, DAN TERNAK SAPI DI KECAMATAN SEMANGGA KABUPATEN MERAUKE, PROPINSI PAPUA - Untari Untari (AGRICOLA, 2011)
The aim of the study was to analyze the effect of production factors on rice, corn far,  cow  breeding in income of farmers. The study was conducted in Semangga District, Merauke Regency, Papua Province. The study was survey the number of samples was 47 respondents. The data were analyzed by using farm analysis and Cobb-Douglas. The results of study indicate that based; 1) factor-factor production the independent variables have and effect on rice is fertilizer 40,9%, for the independent variables not have and effect on production rice is human resource (27%), seed ( l4,l %), pesticide (5,8%). For factor production the independent variables have and effect on com farm is human resource (15,9%), seed (46%), pupuk (31,5%), dan pesticide (10,3%). Were as factor production have effects on cow breeding is cow future 84,5%, as factor production have not effect on production is wefl (0,9 %), human resource (6,6 %), vakcint (4,7%), and medicine (5,9 %). 2) the income farmers corn big more than income from rice farm and cow breeding. The income of farmers for rice is Rp. 4.030.600,50, corn Rp. 19.011.671,88 and for cow Rp. 4.287.410,9. If the farmer cultivates rice, and corn, and beeds cown the profit earned is Rp. 27.329.683,28/periode.